Rural radio let the people be heard ! - Drame, Seydou (Technical Centre for Agricultural and Rural Cooperation, 1990)
Seydou DRAME Is a Burkinabe journalist and a ClERRO (Inter-Afr can Cente for Rural Radio Studies) graduate who has devoted his working of to the promotion of agricultural information. He is a bout to publish a paper on information and the rural...